Acylphloroglucinol-monoterpene meroterpenoids from Eucalyptus tereticornis and their inhibitory activity against ATP citrate lyase. (March 2023) - Li, Jin-Sheng; Liu, Yi-Nan; Li, Jing-Ya; Lei, Chun; Hou, Ai-Jun
Abstract: Five undescribed enantiomeric pairs of acylphloroglucinol-monoterpene meroterpenoids ((+)-/(−)-eucateretins A−E) resolved by chiral-phase HPLC were obtained from the leaves of Eucalyptus tereticornis Smith, along with nine known analogues. Their structures were elucidated by spectroscopic methods and ECD calculations. This is the first report of meroterpenoid enantiomers from this plant. Some of the isolates, (−)-eucateretin A, (+)-/(−)-eucateretins E, 7′ α -eucalrobusone X, eucalrobusone X, and robustadial B, exhibited inhibitory effects on ATP citrate lyase, and 7′ α -eucalrobusone X significantly suppressed the hepatocyte lipogenesis. Graphical abstract: Image 1 Highlights: Nineteen meroterpenoids were isolated from Eucalyptus tereticornis. Five undescribed enantiomeric pairs of meroterpenoids were resolved by chiral HPLC . Some isolates showed inhibition on ATP citrate lyase and hepatocyte lipogenesis.